The Tradition of Qur'anic Murāja'ah: A Living Qur'an Study of the Sholati Ila Mamati Method at Ma'had Aly Baitul Qur'an Wonogiri: Tradisi Murajaah Al-Qur'an: Studi Living Qur’an Metode Sholati Ila Mamati pada Ma'had Aly Baitul Qur'an Wonogiri - Anis Musyafa’ah; Ade Naelul Huda; Samsul Aryadi (Institut Agama Islam Negeri Kerinci, 2026)
The study of Living Qur’an emphasizes how the Qur'an is not merely memorized but actively actualized in daily spiritual practices. This research investigates the Murajaah Sholati Ila Mamati method implemented by students of Ma'had Aly Baitul Qur'an Wonogiri, focusing on its implementation in everyday life, its spiritual effectiveness, and the challenges encountered in its practice. The study aims to describe the method comprehensively, analyze student perceptions, identify supporting and inhibiting factors, and evaluate its contribution to Qur'anic memorization quality. This research employs a mixed-method approach, combining quantitative questionnaire data from 115 students (49 male and 66 female) with qualitative data obtained through in-depth interviews and direct observation. Data were analyzed using descriptive statistical techniques for quantitative data and thematic analysis for qualitative data. The findings reveal that the Murajaah Sholati Ila Mamati method is highly effective in strengthening Qur'anic memorization. Students reported improved memorization quality toward a more mutqin (precise and firmly embedded) level, deepened spiritual experiences during prayer-based murajaah, and enhanced focus and concentration. Internal obstacles such as laziness, forgetfulness, health issues, and poor time management were identified as the primary inhibiting factors (73%), while external challenges including distracting environments and external temptations accounted for 27% of difficulties. This study contributes to the field of Living Qur’an studies by demonstrating that integrating hafalan practice within obligatory and sunnah prayers constitutes an innovative, spiritually enriching, and pedagogically effective method for Qur'anic preservation.